A companion to the historical film - Rosenstone, Robert A.; Parvulescu, Constantin (Malden, MA : Wiley-Blackwell, 2013)
"Broad in scope, this interdisciplinary collection of original scholarship on historical film features essays that explore the many facets of this expanding field and provide a platform for promising avenues of research. Offers a unique collection of cutting edge research that questions the intention behind and influence of historical film. Essays range in scope from inclusive broad-ranging subjects such as political contexts, to focused assessments of individual films and auteurs. Prefaced with an introductory survey of the field by its two distinguished editors Features interdisciplinary contributions from scholars in the fields of History, Film Studies, Anthropology, and Cultural and Literary Studies"--
"Broad in scope, this interdisciplinary collection of original scholarship on historical film features essays that explore the many facets of this expanding field and provide a platform for promising avenues of research"--
20. Heart and Clock: Time and History in The Immortal Heart and Other Films about the Middle Ages / Bettina Bildhauer -- 21. The Anti-Samurai Film / Thomas Keirstead -- pt. 7 Slavery and the Postcolonial World -- 22. The Politics of Cine-Memory: Signifying Slavery in the History Film / David C. Wall -- 23. The African Past on Screen: Moving beyond Dualism / Vivian Bickford-Smith -- 24. Colonial Legacies in Contemporary French Cinema: Jews and Muslims on Screen / Catherine Portuges -- 25."What's Love Got to Do with It?": Sympathy, Antipathy, and the Unsettling of Colonial American History in Film / Louis Kirk McAuley.
Includes bibliographical references and index.
Print version record.
Keywords: Historical films -- History and criticism; Motion pictures and history; PERFORMING ARTS -- Film & Video -- History & Criticism; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; Historical films; Motion pictures and history; Electronic books; Criticism, interpretation, etc